2012
DOI: 10.1371/journal.pgen.1002976
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Arrested Replication Forks by Homologous Recombination Is Error-Prone

Abstract: Homologous recombination is a universal mechanism that allows repair of DNA and provides support for DNA replication. Homologous recombination is therefore a major pathway that suppresses non-homology-mediated genome instability. Here, we report that recovery of impeded replication forks by homologous recombination is error-prone. Using a fork-arrest-based assay in fission yeast, we demonstrate that a single collapsed fork can cause mutations and large-scale genomic changes, including deletions and translocati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
115
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(122 citation statements)
references
References 74 publications
6
115
1
Order By: Relevance
“…The increased mutational complexity included micro-deletions and micro-insertions, apparently originating from DNA polymerase slippage events at the breakpoint junctions (29 %), and small frameshifts or point mutations in homonucleotide runs within the breakpointflanking sequences (13 %; distance to the breakpoints was <45 bp). This increase in mutational complexity has been attributed to the activity of low-fidelity, error-prone DNA polymerases used during DNA repair via replication-based mechanisms (Carvalho et al 2013), a conclusion supported by multiple previous studies (Arlt et al 2012;Deem et al 2011;Hicks et al 2010;Iraqui et al 2012;Shah et al 2012;Smith et al 2007). Somewhat unexpectedly, all three of our disease-causing deletion CNVs, when characterized at the nucleotide level, were found to have cis-linked additional mutations.…”
Section: Discussionsupporting
confidence: 80%
“…The increased mutational complexity included micro-deletions and micro-insertions, apparently originating from DNA polymerase slippage events at the breakpoint junctions (29 %), and small frameshifts or point mutations in homonucleotide runs within the breakpointflanking sequences (13 %; distance to the breakpoints was <45 bp). This increase in mutational complexity has been attributed to the activity of low-fidelity, error-prone DNA polymerases used during DNA repair via replication-based mechanisms (Carvalho et al 2013), a conclusion supported by multiple previous studies (Arlt et al 2012;Deem et al 2011;Hicks et al 2010;Iraqui et al 2012;Shah et al 2012;Smith et al 2007). Somewhat unexpectedly, all three of our disease-causing deletion CNVs, when characterized at the nucleotide level, were found to have cis-linked additional mutations.…”
Section: Discussionsupporting
confidence: 80%
“…For example, a recent study showed that Sgs1 foci are reduced after HU treatment in a Slx8-dependent manner (Bohm et al 2015). At a protein-mediated stall, the restarted fork was more prone to replication slippage, producing deletions (Iraqui et al 2012). A similar fork restart mechanism could be occurring at the CAG repeat, contributing to the low level of instability, biased toward contractions, that is observed in unperturbed wild-type cells (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Recent results show that replication in the context of HR repair or HR-dependent fork restart proceeds with less fidelity and more mutations than normal replication, even without the complication of copying DNA repeats (Deem et al ., 2011; Hicks et al ., 2010; Iraqui et al ., 2012). Recently, GAA repeats have been shown to induce mutagenesis up to 8 kb from the repeat site in yeast, which is enhanced in strains with polymerase defects and largely dependent on the Polζ TLS polymerase (Saini et al ., 2013; Shah et al ., 2012; Tang et al ., 2013).…”
Section: The Role Of Dsb Repair In Preventing Repeat Fragility and Inmentioning
confidence: 99%